Nontraditional crops and land accumulation among Guatemalan smallholders: is the impact sustainable? - Carletto, Calogero (International Food Policy Research Institute, 2000)
Since the late 1970s dramatic economic changes have taken place in the agricultural sector in the highlands of Guatemala. The introduction of new export crops, such as snow peas, broccoli, and miniature vegetables, has led to yet another agro-export boom. Unlike earlier booms, however, this one has included all but the smallest farmers. The high rate of smallholder participation in the boom, and the initial high profitability of nontraditional exports (NTXs), fueled initial optimism that NTX production could increase smallholders’ ability to accumulate land and so decrease the highly skewed distribution of land in Guatemala, a country with one of the most unequal landholding patterns in all of Latin America. The picture that emerges from the analysis in this paper raises serious questions about the sustainability and equity effects of NTX crop adoption among smallholders in the long run. Two main findings illustrate the problems besetting NTX crop production. First, the land accumulation rates of adopters have dropped dramatically in the 1990s. NTX crop adopters accumulated close to three times more land than non-adopters in the 1980s. Although adopters are still accumulating more land than non-adopters in the 1990s, the gap between the two groups has narrowed substantially. Second, smaller adopters are no longer accumulating land at higher rates than their larger counterparts. In the 1980s the landholdings of smaller adopters grew significantly faster than those of the larger adopters, but this trend reversed itself in the1990s. The advantages smallholders initially had in accumulating land may have been lost as a result of deteriorating agronomic conditions and volatile export markets.